1983
DOI: 10.1111/j.1365-2125.1983.tb01561.x
|View full text |Cite
|
Sign up to set email alerts
|

Delta‐9‐tetrahydrocannabinol and gastric emptying.

Abstract: The effects of delta‐9‐tetrahydrocannabinol (0.5 and 1 mg i.v.) on gastric emptying of liquid were investigated in seven normal volunteers and compared with placebo. Despite significant change in pulse rate and psychological parameters consistent with cannabis activity there was no significant effect on the pattern of gastric emptying. It is therefore suggested that an anti‐emetic action of delta‐9‐tetrahydrocannabinol does not involve a change in gastric emptying.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…In contrast, Bateman found that gastric emptying of liquid, measured by real time ultrasound, was unaffected by Δ 9 ‐THC (0.5 and 1 mg i.v.) in seven fasted cannabis‐naive male volunteers 33 . The different conclusions derived from these studies might be due to the methodology or to differences in prior exposure to cannabis.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…In contrast, Bateman found that gastric emptying of liquid, measured by real time ultrasound, was unaffected by Δ 9 ‐THC (0.5 and 1 mg i.v.) in seven fasted cannabis‐naive male volunteers 33 . The different conclusions derived from these studies might be due to the methodology or to differences in prior exposure to cannabis.…”
Section: Discussionmentioning
confidence: 94%
“…McCallum et al 32 . studied the gastric emptying of a radiolabelled solid meal, whereas Bateman 33 studied gastric emptying of liquid measured by ultrasound. McCallum et al 32 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The trial was randomised and double blind, and was performed with nine male and four female experienced cannabis users. In contrast, Bateman60 found that gastric emptying, monitored by a real time ultrasound technique, was unaffected by Δ 9 -THC in seven fasted cannabis naive male volunteers that had consumed 500 ml of warm orange cordial 30 minutes after injection. The doses of Δ 9 -THC used in this study (0.5 and 1 mg intravenously) increased pulse rate and produced cannabis-like psychomotor and psychological effects.…”
Section: Cannabinoids Delay Gastric Emptying In the Whole Animalmentioning
confidence: 92%